All meromorphic solutions of an auxiliary ordinary differential equation and its applications. Issue 5 (September 2015) - YUAN, Wenjun; XIONG, Weiling; LIN, Jianming; WU, Yonghong
Abstract In this paper, we first employ the complex method to deritive all meromorphic solutions of an auxiliary ordinary differential equation, and then find all meromorphic exact solutions of the modified ZK equation, modified KdV equation, nonlinear Klein-Gordon equation and modified BBM equation. Our work shows that there exist some classes of rational solutions wr, 2(z) and simple periodic solutions ws, 1(z) which are new and are not degenerated successively to by the elliptic function solutions.